Epistemological analysis of Special Education in Costa Rica - Castillo Cordero, Karla (2018)
This article has been developed to socialize the research results obtained by the Inter-Institutional Committee of Epistemology Analysis of the Special Education in Costa Rica. It aimed to answer questions such as; what does Special Education means in this historic moment? Where should it go as a discipline? What should be the role of the special educator in the coming years? In order to respond to these questions, it was necessary to perform two academic meetings of epistemological analysis with several different actors linked with Special Education, whose shares were registered and studied among qualitative hermeneutic strategies. The group of participants was divided in groups using the Meta action methodology to reflect on the proposed topic. It was concluded that the Special Education needs to be systematically transform in the light of the inclusive education principles, the services offered to the students needs to be reorganized, and it is needed to eliminate practices that respond to the deficit of students with disabilities. Finally, it calls to eliminate segregation practices toward this group of students. To achieve these changes, it is necessary to articulate efforts among different instances; such as universities, the Ministry of Public Education, families, and schools within the system. The reflex ions offered are just the first attempt to rethink the epistemology of the current Special Education discipline, aiming to generate changes to achieve an equal education for all students.